2020
DOI: 10.4103/jfmpc.jfmpc_99_20
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of association of serostatus and extra-articular manifestations in patients with rheumatoid arthritis in a teaching hospital

Abstract: Background: Rheumatoid arthritis (RA) is an autoimmune disease, which mistakenly attacks the joints and induces the inflammatory changes that thicken the joints (the synovium) resulting in swelling and pain in and around the joints. It causes pain, joint deformity, and also affects the quality of life. The joint is affected symmetrically. It also can affect body systems, such as the cardiovascular, respiratory systems, or other systems, which manifest as extra-articular manifestations. Extra-artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…Our finding was like many other studies that showed increasing duration has strong association with extra articular manifestations. 14,28,29 Very rarely noted findings in our study was felty syndrome <1%, osteoporosis. No single case was noted for amyloidosis.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…Our finding was like many other studies that showed increasing duration has strong association with extra articular manifestations. 14,28,29 Very rarely noted findings in our study was felty syndrome <1%, osteoporosis. No single case was noted for amyloidosis.…”
Section: Discussionmentioning
confidence: 51%
“…Mean age of patients in my study was 39 years and most of patients belong to age group of 31-45 years, which was also comparable to other studies. 13,14 Our study has strong correlation of seropositivity with extra articular manifestations, having statistically significant importance (p value: <0.01). Shankar S et al 15 and others found that up to 80% of patients were seropositive rheumatoid arthritis in their studies during assessment of extra articular manifestations.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Interestingly, the incidence of PN varied according to the different subtypes of RA. Kumar et al [50] reported that the prevalence of PN in seropositive RA patients and seronegative RA patients was 34.4% vs. 15.4, respectively. Further studies are required to clarify the clinical and pathological relationships between seropositive and seronegative RA patients.…”
Section: Rheumatoid Arthritis (Ra)mentioning
confidence: 99%